Selective ablation of mast cells or basophils reduces peanut-induced anaphylaxis in mice - Reber, Laurent L. (2013)
BACKGROUND: Studies using c-kit mutant mast cell (MC)-deficient mice and antibody-mediated depletion of basophils suggest that both MCs and basophils can contribute to peanut-induced anaphylaxis (PIA). However, interpretation of data obtained using such approaches is complicated because c-kit mutant mice have several phenotypic abnormalities in addition to MC deficiency and basophil-depleting antibodies can also react with MCs. OBJECTIVE: We analyzed: (1) the changes in the features of PIA in mice after the selective and inducible ablation of MCs or basophils, and (2) the possible importance of effector cells other than MCs and basophils in the PIA response. METHODS: Wild-type (WT) and various mutant mice were orally sensitized with peanut extract and cholera toxin weekly for 4 weeks and challenged intraperitoneally with peanut extract 2 weeks later. RESULTS: Peanut-challenged MC-deficient Kit(W-sh/W-sh) mice developed reduced immediate hypothermia, as well as a late phase drop in body temperature that was abrogated by antibody-mediated depletion of neutrophils. Diphtheria toxin-mediated selective depletion of MCs or basophils in Mcpt5-Cre; iDTR and Mcpt8(DTR) mice, respectively, and treatment of WT mice with the basophil-depleting antibody Ba103, significantly reduced peanut-induced hypothermia. Non-c-kit mutant MC- and basophil-deficient Cpa3-Cre; Mcl-1(fl/fl) mice developed reduced, but still significant, responses to peanut. CONCLUSION: Inducible and selective ablation of MCs or basophils in non-c-kit mutant mice can significantly reduce PIA, but partial responses to peanut can still be observed in the virtual absence of both cell types. The neutrophilia in Kit(W-sh/W-sh) mice may influence the responses of these mice in this PIA model.